The epidemiology of intermittent and chronic ataxia in children in Manitoba, Canada. - Salman, Michael S; Lee, Esther J; Tjahjadi, Anindita; Chodirker, Bernard N (Developmental Medicine & Child Neurology, 2013)
AIM: To determine the epidemiology of chronic ataxia in children in Manitoba, Canada. METHOD: A retrospective study using multiple sources and disease codes identified children (age 0-16y) with chronic ataxia (>2mo duration or recurrent episodes of ataxia) seen at Winnipeg Children's Hospital from 1991 to 2008. Patients with isolated peripheral nerve diseases, vestibular disorders, or brain tumors were excluded. RESULTS: We identified 184 patients (males=females; mean age 15y, SD 7y 8mo) with chronic ataxia. Median age at the presenting symptom onset was 1 year 3 months and at ataxia onset 3 years 1 month. Median duration of follow-up was 6 years 5 months. During the study period, the crude incidence rate was 5.77 in 10 000; the crude prevalence rate was 6.59 in 10 000; and the crude mortality rate 0.446 in 10 000. The most common presenting symptoms were developmental delay, ataxia, or seizures. The most common diagnoses (known in 129) were Angelman syndrome (n=16), ataxia telangiectasia (n=13), mitochondrial disease (n=9), Friedreich ataxia (n=7), stroke (n=7), and familial/genetic episodic ataxia (n=7). INTERPRETATION: Chronic ataxia is a relatively common early-presenting symptom in childhood. A specific diagnosis is possible in 70% of patients after extensive investigations. The mortality rate is relatively low and the disease burden is high with significant comorbidities including developmental delay and epilepsy.